The Impact of Marketing Communication Mix on Business Results of Micro, Small and Medium Enterprises (MSMEs) - Isnaeni, Fajar (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Communication marketing have impact positive on every aspect operation business. They in a way significant influence How economy in the end. Research purposes This is For investigate How components certain from mix communication marketing influence performance part business small and medium in Surabaya. Development and distribution primary data collection has been reach owner and manager SME survey. Influence element communication certain advertising, promotion sales, and marketing straight on some metric financ , incl profit , sales , and profitability company , identified in study This through use methodology descriptive and procedural informal research . Findings This show significant relationship​ in a way statistics between indicator finance like profit and income sale clean as well as advertising and promotions sale. SME managers accept recommendation about various topics, incl method best using media, giving information and information latest to consumer through channel communication, and doing activity promotion.